The unfinished nation : a concise history of the American people - Brinkley, Alan. (Boston : McGraw-Hill, 2000)
The meeting of cultures. The English 'Transplantations". Society and culture in provincial America. The empire under strain. The American revolution. The constitution and the new republic. The jeffersonian era. Jacksonian America. America's economic revolution...
Keywords: United States; United States -- History; United States -- History